Just and unjust peace: an ethic of political reconciliation - Philpott, Daniel (Studies in strategic peacebuilding, 2012)
Whose justice? -- The basic standards of justice -- The wounds of political injustice -- Reconciliation as a concept of justice -- Is reconciliation fit for politics? -- Is religion fit for reconciliation? -- Reconciliation in the Jewish tradition -- Reconciliation in the Christian tradition -- Reconciliation in the Islamic tradition -- Four practices : building socially just institutions, acknowledgment, reparations, and apologies -- Punishment -- Forgiveness